Molecular Docking: Study of Chalcone Derivatives from Boesenbergia pandurata Targeting Estrogen Receptor Alpha (ER–a) for Breast Cancer - Marsha Anggita Amelia; Dini Kesuma; Aguslina Kirtishanti; I Gede Ari Sumartha; Maria Claudya (Jurnal Penelitian Pendidikan IPA, 2024)
The increasing number of cancer patients and the challenge of multidrug resistance (MDR) demand more effective drugs, which can be developed by modifying compounds derived from natural resources, such as the flavonoid-rich temu kunci rhizome (Boesenbergia pandurata (Roxb.) Schlecht.). This study aims to predict the cytotoxicity and toxicity of 20 Pinostrobin derivatives and 19 Chalcone derivatives as potential anticancer candidates. Estrogen receptor alpha (ER-α), a validated cancer therapy target, was used for molecular docking in in silico tests using Molecular Graphics Laboratory (MGL) Tools (including, AutoDock Vina, AutoDock Tools 4.1, and Python 2.5.2) and PyRx Program. Toxicity was predicted using the pkCSM program and Protox online tool. The docking process involved binding the compounds to ER-α (PDB IDs 6CHZ and 3ERT), with the binding energy indicating activity; lower binding energy values suggest greater cytotoxic potential and stronger ligand-receptor interactions. The results showed that Chalcone derivatives from temu kunci exhibited lower toxicity and higher cytotoxic activity compared to Pinostrobin derivatives and the reference compound, Tamoxifen (TAM). Notably, Bis-3-chlorobenzyloxychalcone and Bis-2-chlorobenzyloxychalcone demonstrated the highest predicted cytotoxic activity. In conclusion, Chalcone derivatives are promising candidates for further development as more effective anticancer drugs, especially those that outperform Tamoxifen. These findings highlight the potential of natural compounds, particularly Chalcone derivatives, in combating cancer while addressing the growing challenge of MDR in clinical treatments.